1984
DOI: 10.1002/1097-4679(198401)40:1<115::aid-jclp2270400120>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and the MMPI: A cross-validation of predictors

Abstract: Compared a suicide-completion group to a psychiatric control sample on the 13 traditional MMPI scales, three experimental item pools, and eight profile patterns earlier described as indicative of suicidal tendencies ( N = 84). Also compared the frequencies with which the groups endorsed each of the 566 MMPI items. The number of resulting significant differences was less than chance. The results argue against the use of the MMPI to predict suicide at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…The higher scores obtained by both completers and attempters on the Mf scale is in keeping with what has been observed in previous studies (Kincel, 1983;Leonard, 1977;Waters et al, 1982;Watson et al, 1984). However, the scores on other scales are more surprising, as they suggest that attempters are more pathological than the others.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The higher scores obtained by both completers and attempters on the Mf scale is in keeping with what has been observed in previous studies (Kincel, 1983;Leonard, 1977;Waters et al, 1982;Watson et al, 1984). However, the scores on other scales are more surprising, as they suggest that attempters are more pathological than the others.…”
Section: Discussionsupporting
confidence: 83%
“…High scores on the Mf or Pd scale (Kincel, 1983) or only on the Mf scale (Leonard, 1977;Waters, Sendbuehler, Kincel, & Boodoosingh, 1982;Watson, Klett, Walters, & Vassar, 1984) have been found to be related to suicidal behavior, although these results have not always been replicated. For example, in the Kinsinger (1973) study, the Mf scale was the only one not to discriminate among the groups.…”
Section: Use Of the Mmpi To Understand And Predict Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…In another study, 65% of the suicide attempters among epileptics used antiepileptic drugs, 60% of which were barbiturates (Hawton et al, 1980). Finally, Luscomb, Clum, and Patsiokas (1980) reported that suicide attempters subjectively experienced three times as much stress as nonsuicidal psychiatric patients.Although recent efforts to develop predictors of suicide have been unsuccessful when applied to individual cases (Porkorny, 1983;Watson, Klett, Walters, & Vassar, 1984), researchers point to the need in clinical practice for variables that have been found to be related significantly to suicide or suicide attempts in assessing the "suicidal patient" (Porkorny, 1983). The present study investigated the emotional and intellectual correlates of unsuccessful suicidal behavior in adults with epilepsy in an effort to identify such variables.…”
mentioning
confidence: 91%
“…Although recent efforts to develop predictors of suicide have been unsuccessful when applied to individual cases (Porkorny, 1983;Watson, Klett, Walters, & Vassar, 1984), researchers point to the need in clinical practice for variables that have been found to be related significantly to suicide or suicide attempts in assessing the "suicidal patient" (Porkorny, 1983). The present study investigated the emotional and intellectual correlates of unsuccessful suicidal behavior in adults with epilepsy in an effort to identify such variables.…”
mentioning
confidence: 99%